On evaluation of high burnout performance in a rocket-engine-based incinerator for solid-particles burning. (1st December 2016) - Son, Jin Woo; Lee, In Ho; Kim, Chul Jin; Sohn, Chae Hoon
Highlights: Burning performance of solid wastes is evaluated experimentally in the RBI chamber. The measured burning rates are in a good agreement with the calculated ones. The burnout ratio based on CO2 mole fraction is verified by comparative studies. High burning rate of the RBI shows feasibility in rapid burning of solid wastes. Abstract: To dispose of solid biomass particles such as wood, municipal solid wastes (MSW), and animal carcass, burning of solid particles in the chamber of a rocket-engine-based incinerator (RBI) was suggested for the purposes of both high-performance burnout and mobility. For high burning performance, the chamber of an RBI has the shape of a rocket combustor and in-chamber swirl flow is formed by peripheral injectors. But, its high burnout performance was verified by only numerical analyses without experimental evidence. In this study, both burning tests and simulations are conducted for several operating conditions with a target performance, which is higher than that of conventional incinerators by a factor of 10. For the tests, bituminous coal is employed as a simulant fuel for solid particles from wastes. It is supplied into the chamber with air as in previous numerical simulations. The calculated burning rate of coal particles is validated by a measured one, which confirms the feasibility of higher burning rate with an RBI by one order of magnitude than with conventional incinerators or boilers. Burnout ratio, a quantitative parameter for burnout performance, is evaluated numerically and experimentally for a comparative study. For experimental evaluation of burning performance, burnout ratio based on CO2 mole fraction is suggested and verified. Gaseous methane is supplied into the chamber to facilitate ignition of solid particles and its co-burning with coal affects burnout ratio significantly, which is increased by around 15% when methane of 20% is fed in mole fraction.